ORGANOMINERAL NA CULTURA DA SOJA - Sordi, André; Dallagnol, Eduardo; Reiter, Laura; Baldo, Raul (Anuário Pesquisa e Extensão Unoesc São Miguel do Oeste, 2024)
Cultivares de soja submetidas a doses de organomineral